A ‘Shared’ Experience of Constituent Power: The Legal Culture of Some Legal Scholars and Constituents in the de facto Chilean Constitution (2025)
‘Constituent power’ is usually associated with the exercise of some kind of force, whether legitimate or not, or to amending an existing text through established procedures. However, setting the constitutional machinery in motion sometimes requires more than a text to be accepted by society and legal operators. This is especially true when a new constitution results from an institutional breakdown. We will refer to this conjunction of necessities as ‘shared’ constituent power. With this idea in mind, this paper analyzes the impact, on chilean legal culture, of those who participated in the creation and teaching of the 1980 Constitution during its first years of its implementation. Using the concept of internal legal culture, the author seeks to show how the exercise of the de facto constituent power required the collaboration of a set of bodies in general, but specially of a group of academics to create, inform, and reinforce the ideas contained in the new constitution. They fulfilled a dual role: they were the architects of some of the foundations of the new constitutional text, and they taught the ideologies to model the beliefs about institutionality needed by those who broke it after the 1973 coup d’état.